Alkaline hydrolysis of radio-oxidized aliphatic polymers. (July 2020) - Ferry, M.; Dannoux-Papin, A.; Legand, S.; Exposito, E.; Durand, D.; Ngono-Ravache, Y.; Esnouf, S.
Abstract: Organic molecules are part of the Long-Lived Intermediate-Level Waste (LL-ILW) packages. These packages are planned to be delivered at the French deep geological repository, consequently their degradation has to be thoroughly understood in order to support the safety studies. In a first period, these organic molecules, which include polymers, are radio-oxidized because of their close proximity with radionuclides. In a second period, water will diffuse inside the site up to the packages, leading to the alkaline hydrolysis of the radio-oxidized polymers. The objective of this study is to evaluate the parameters having a major influence on these radio-oxidized polyolefins hydrolysis at high pH. Aliphatic polymers are chosen because of their relative importance, in quantity, in the French LL-ILW packages. In this work, we have first radio-oxidized aliphatic polymers in conditions that are representative of their ageing in the first period of the LL-ILW packages: we have employed different doses up to 10 MGy, different emitters - or their equivalent -, i.e. γ-rays and swift heavy ions (SHI) irradiation to model α-rays. To model the second period of ageing of these LL-ILW packages, we have hydrolyzed under alkaline conditions and under inert atmosphere these radio-oxidized polymers. We have evaluated the influence of the materials' composition (the resin chemical structure, presence of charges and fillers) and of the irradiation conditions (irradiation type, linear energy transfer (LET) and dose). We observed that hydrolysis is influenced not only by the molecular structure of the polymer, but also by the presence of inorganic fillers and organic additives. The hydrolysis increases with increasing dose and increasing LET for SHI. The most penalizing conditions were encountered under low LET ionizing rays. This is related to the higher oxidation level induced under γ-rays: the higher the oxidation rate, the higher the polyolefins sensitivity to alkaline hydrolysis. Highlights: The sensitivity of irradiated polyolefins to alkaline hydrolysis has been evaluated. Degradation increases with increasing LET and increasing dose. Degradation decreases in presence of additives. Most penalizing conditions are encountered using low LET ionizing rays. The higher the oxidation rate, the higher the polyolefins sensitivity to hydrolysis.